The will of the people the revolutionary birth of America - Breen, T. H. (Harvard University Press, 2019)
Over eight years of war, ordinary Americans accomplished something extraordinary. Far from the actions of the Continental Congress and the Continental Army, they took responsibility for the course of the revolution. They policed their neighbors, sent troops and weapons to distant strangers committed to the same cause, and identified friends and traitors. By taking up the reins of power but also setting its limits, they ensured America's success. In this strikingly original account, Breen restores these missing Americans to our founding and shows why doing so is essential for understanding why our revolution ended differently from other revolutions that have shaped the modern world. In the face of revolution's anger, fear, and passion--forgotten elements in effective resistance--these Americans preserved a political culture based on the rule of law. In the experiences of these unsung revolutionaries can be seen the creation of America's political identity.--